EXPERIMENTAL STUDY OF THE DYNAMIC BEHAVIOR OF A BEAM WITH SPATIALLY CORRELATED MASSES FOR DIFFERENT RANDOM FIELD MODELS - S. Travi, Matheus (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
There is no such thing as absence of variability in manufacturing processes. Therefore, there is a need for improved prediction models which take this variability into account. Experimental studies of these variabilities often are complex and hardly found in the literature mainly because the characterization of a great number of samples has a high cost associated and the variability model can only be defined after the samples are produced. In this work, an experimental setup capable of imposing a spatially correlated variability model a priori is used. The mass density distribution of a straight beam is approximated by small and evenly distributed masses whose values are given by a random field model. The masses are small magnets attached to the beam, allowing for easily changing the distribution and providing a great number of samples. Different configurations of masses are generated from different discrete random field models, i.e. with different PDFs, correlation functions and lengths. For each configuration, an ensemble of dynamic responses is measured from an impact hammer test and effects of the different random field configurations on the statistic of the bending natural frequencies of the beam are investigated.